Seed content and its oil composition in walnut cultivated from Tunceli, Türkiye - Çağlar Mert Aydın; Alper Güven (Cogent Food & Agriculture, 2024)
The study is intended to shed light on walnut species cultivated in Tunceli province in 2022 and the oils produced from Juglans regia Fernor walnuts. Physicochemical properties of walnuts and fatty acid composition of the oils produced from the walnuts were identified. In addition, nutritional indexes and bioactive compounds of the oils were determined.Overall, physicochemical properties of the seeds belonging to walnuts significantly changed according to the variety. The major component in walnut seeds was found to be oil content. Saturated (SFA), monounsaturated (MUFA) and polyunsaturated (PUFA) fatty acid ratios of the walnuts were varied according to the type of seed. Characterization of fatty acid composition in the oils from the walnuts was performed according to 6 different fatty acid levels. These fatty acids are myristic, palmitic, margaric, oleic, linoleic and linolenic acid. The oils have a refractive index being in the range of 1.4677–1.4694, the iodine value being in the range of 107–109 gms. TPC (total phenolic content) and DPPH antioxidant activity of the oils significantly changed according to the variety. TPC of the oils were found in the range of 0.33–1.53 mg GAE/g oil and DPPH antioxidant activity of the oils were in the range of 13.04–5.42 mg TE g−1 oil. All walnut oils showed Newtonian flow behavior. The nutritional indexes including UI (Unsaturation index), IA (Atherogenicity index), IT (Thrombogenicity index) and HH (Hypocholesterolemic/hypercholesterolemic ratio) were determined to significantly change according to the variety, except for IT. It could be stated from the results that Nazimiye walnut seed oil has healthier effects on human health.